The Patterns of Agroforestry and Its Contribution to the Community Income - Emi Roslinda; Fransiska Wiwi Prisila; Yeni Mariani (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Farmers choose an agroforestry pattern to fulfill various objectives, including obtaining their income. The diversity of fruit plants chosen by the Nanga Menterap village community as a component of the agroforestry system has the potential to contribute significantly as a source of community income. This research aimed to describe the agroforestry patterns and calculate the contribution of agroforestry patterns to the income of the people of Nanga Menterap Village, West Kalimantan Province, Indonesia. The research used a survey method by census. Data collection techniques included observation, questionnaires, and interviews with the Nanga Menterap Village community with agroforestry land. The agroforestry pattern in Nanga Menterap Village can be classified into two types: the agrisilvicultural and the agrosilvopastural. Farmers in Nanga Menterap Village apply a random mixture planting form in which crops and trees are planted irregularly. The agroforestry plants combined in the forestry component include durian (Durio zibethinus), aren (Arenga pinnata), tengkawang (Shorea stenoptera), mango (Mangifera indica), jackfruit (Artocarpus heterophyllus), and petai (Parkia speciosa). The agricultural component includes chili (Capsicum annuum), cocoa (Theobroma cacao), corn (Zea mays), coconut (Cocos nucifera), coffee (Coffea robusta), banana (Musa sp.), cassava (Manihot esculenta), long bean (Vigna unguiculata), ginger (Zingiber officinale), turmeric (Curcuma longa Linn. syn. Curcuma domestica Val.), eggplant (Solanum melongena), and tomatoes (Solanum lycopersicum), while the types of livestock such as pigs, domestic chickens, cows, and goats. The contribution of agroforestry to community income in Nanga Menterap Village is 82.74%. From these contributions, the agroforestry system is the right choice for the community and government to manage land. The governments should be able to facilitate and determine specific and targeted activity programs to improve the cultivation capabilities and welfare of farmers. Keywords: agroforestry, community, contribution, income